Influences of NaCl and Na2SO4 on the Micellization Behavior of the Mixture of Cetylpyridinium Chloride + Polyvinyl Pyrrolidone at Several Temperatures - Md. Farid Ahmed; Malik Abdul Rub; Md. Tuhinur R. Joy; Mohammad Robel Molla; Naved Azum; Md. Anamul Hoque (Gels, 2022)
Herein, the conductivity measurement technique is used to determine the interactions that may occur between polyvinyl pyrrolidone (PVP) polymer and cetylpyridinium chloride (CPC) surfactant in the presence of NaCl and Na2SO4 of fixed concentration at variable temperatures (298.15–323.15 K) with an interval of 5 K. In the absence or presence of salts, we observed three critical micelle concentrations (CMC) for the CPC + PVP mixture. In all situations, CMC1 values of CPC + PVP system were found to be higher in water than in attendance of salts (NaCl and Na2SO4). Temperature and additives have the tendency to affect counterion binding values. Various physico-chemical parameters were analyzed and demonstrated smoothly, including free energy (ΔG0m), enthalpy (ΔH0m) and entropy change (ΔS0m). The micellization process is achieved to be spontaneous based on the obtained negative ΔG0m values. The linearity of the <semantics>Δ<msubsup>Hmo</msubsup></semantics> and <semantics>Δ<msubsup>Smo</msubsup></semantics> values is excellent. The intrinsic enthalpy gain (ΔH0*m) and compensation temperature (Tc) were calculated and discussed with logical points. Interactions of polymer hydrophobic chains or the polymer + surfactant associated with amphiphilic surface-active drugs can employ a strong impact on the behavior of the gels.